Services trade costs Tariff equivalents of services trade restrictions using gravity estimation - Benz, Sebastian (OECD Trade Policy Papers, 2017)
Estimates for ad valorem tariff equivalents of services trade restrictions for cross-border trade in six services sectors are presented in this paper. These equivalents are found to be very big in several service sectors with estimates ranging as high as 2000% when trade flows are relatively inelastic, as opposed to between 20% and 300% in most other sectors. The results indicate that trade costs may even increase less than proportionally as the degree of services trade restrictiveness rises. In addition, the paper shows that services trade liberalisation has the largest effect on trade flows in smaller markets. The estimates presented in this Paper are based on a gravity framework using data on both bilateral trade flows and on the value of domestic production. Production values are used to construct measures for the domestic consumption of domestic services in each country, which enables country-specific trade restrictions to be identified, while controlling for multilateral resistance using fixed effects